Apoio à mulher para a amamentação e o papel do profissional da atenção primária no suporte ao aleitamento materno - Peres, Janaine Fragnan (2020)
Breastfeeding is an important social practice for children, women and the country. However, their rates in Brazil are below those recommended by the World Health Organization, pointing out that this process is influenced by numerous determinants that act in the biopsychosociocultural context, in which the woman is inserted. Therefore, the objective was to identify the source of primary support for women during pregnancy, to assess the quality of this relationship with a view to supporting breastfeeding, and to understand the perceptions of health professionals about breastfeeding support, covering biopsychosociocultural factors related to food childish. This was a qualitative, quantitative, descriptive and exploratory study carried out in health units in a municipality in western Paraná. The quantitative approach was carried out by sampling convenience with 152 pregnant women of habitual and / or intermediate risk and the data were collected through the application of the scale “Quality of the relationship with close people”, in addition to an instrument for characterizing the participants. The qualitative approach took place with 28 health professionals through semi-structured interviews. Quantitative data were systematized and statistically analyzed in a descriptive manner. Qualitative data were analyzed using thematic analysis and discussed in the light of the health promotion framework. The pregnant women identified the husband / partner and other family members as the people who act as their primary source of support. The total evaluation of the scale showed an average of 103.5, ranging from 40 to 128, and Cronbach's alpha value of 0.89. It was found that the quality of this relationship with the person close is healthy and positive aspects predominate. Health professionals declared themselves to be the main source of support for women during breastfeeding and the family nucleus was rarely mentioned in the speeches; identified that mixed breastfeeding is the most adopted practice until the six months of life of the newborn and that maternal work acts as the main barrier that prevents the practice of exclusive breastfeeding. Aspects of biological, cultural and professional intervention also emerged as barriers. However, several biopsychosociocultural factors that interfere with exclusive breastfeeding were not considered as the cause of exclusive breastfeeding and early weaning. However, professionals recognize the weaknesses in their care practice and point out the need for qualifications and training to work in this context. It is concluded that the scale presents a solid method to measure the quality of a relationship with a close person, because when its results are positive, the greater the support received by the pregnant woman and, consequently, the greater the influences for the woman to initiate and perpetuate the exclusive breastfeeding. However, health professionals need to identify that breastfeeding is determined by numerous factors and that people in the social context of the nursing mother are influencers of this practice. The importance of qualified primary care health professionals is demonstrated and prepared to support women and their families in the breastfeeding process and permanent education actions involving this theme in the daily lives of health teams are suggested.